Soil erosion assessment on hillslope of GCE using RUSLE model - Islam, Md Rabiul; Jaafar, Wan Zurina Wan; Lai, Sai Hin; Osman, Normaniza; Din, Moktar Aziz Mohd; Zuki, Fathiah Mohamed; Srivastava, Prashant; Islam, Tanvir; Adham, Md Ibrahim (Indian Academy of Sciences, 2018)
A new method for obtaining the C factor (i.e., vegetation cover and management factor) of the RUSLE model is proposed. The method focuses on the derivation of the C factor based on the vegetation density to obtain a more reliable erosion prediction. Soil erosion that occurs on the hillslope along the highway is one of the major problems in Malaysia, which is exposed to a relatively high amount of annual rainfall due to the two different monsoon seasons. As vegetation cover is one of the important factors in the RUSLE model, a new method that accounts for a vegetation density is proposed in this study. A hillslope near the Guthrie Corridor Expressway (GCE), Malaysia, is chosen as an experimental site whereby eight square plots with the size of 8 × 8 and 5 × 5 m are set up. A vegetation density available on these plots is measured by analyzing the taken image followed by linking the C factor with the measured vegetation density using several established formulas. Finally, erosion prediction is computed based on the RUSLE model in the Geographical Information System (GIS) platform. The C factor obtained by the proposed method is compared with that of the soil erosion guideline Malaysia, thereby predicted erosion is determined by both the C values. Result shows that the C value from the proposed method varies from 0.0162 to 0.125, which is lower compared to the C value from the soil erosion guideline, i.e., 0.8. Meanwhile predicted erosion computed from the proposed C value is between 0.410 and 3.925tha-1yr-1 compared to 9.367 to 34.496tha-1yr-1 range based on the C value of 0.8. It can be concluded that the proposed method of obtaining a reasonable C value is acceptable as the computed predicted erosion is found to be classified as a very low zone, i.e. less than 10tha-1yr-1 whereas the predicted erosion based on the guideline has classified the study area as a low zone of erosion, i.e., between 10 and 50tha-1yr-1.